2014
DOI: 10.1007/s11060-014-1364-y
|View full text |Cite
|
Sign up to set email alerts
|

CXCL12 secreted from glioma stem cells regulates their proliferation

Abstract: Emerging evidence suggests that the chemokine CXCL12 and its receptor CXCR4, which are expressed by glioma stem cells (GSCs), play an important role in tumorigenesis. To provide evidence for establishing a new therapy targeting the CXCL12/CXCR4 pathway, we investigated whether CXCL12 secreted from GSCs contributed to their proliferation and promoted angiogenesis in murine GSCs. Angiogenetic functions and proliferation of GSCs with or without CXCL12 inhibitors were evaluated in an in vitro model using tube form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…CXC chemokines are also involved in several types of CSC growth. CXCL12 (SDF1) is the best investigated chemokine among the CSC studies, and it promotes glioma stem cell proliferation and regulates the glioblastoma microenvironment3435. The CXCL12-CXCR4 axis regulates the growth and invasion of ovarian CSCs3637.…”
Section: Discussionmentioning
confidence: 99%
“…CXC chemokines are also involved in several types of CSC growth. CXCL12 (SDF1) is the best investigated chemokine among the CSC studies, and it promotes glioma stem cell proliferation and regulates the glioblastoma microenvironment3435. The CXCL12-CXCR4 axis regulates the growth and invasion of ovarian CSCs3637.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, GBM CSC proliferation was induced either by treatment with exogenous CXCL12 (Liu et al, 2013) or by the receptor activation induced by CXCL12 secreted by CSCs in an autocrine fashion (Uemae et al, 2014). This effect was mainly mediated by CXCR4, since it was reversed in the presence of the CXCR4 antagonist AMD3100 (Schulte et al, 2011; Gatti et al, 2013).…”
Section: Cxcl12 Cxcr4–cxcr7 Activity In Human Glioblastoma Stem-likementioning
confidence: 99%
“…In particular, knocking down CXCR4 using RNAi or inhibiting CXCR4 function by AMD3100 in CSCs, impairs proliferation in vivo , effectively reducing tumor growth in two different xenograft models (Ping et al, 2011; Lee et al, 2013); similarly shRNA CXCL12 knock-down in CSCs inhibited tumor growth in vivo (Uemae et al, 2014). …”
Section: Cxcl12 Cxcr4–cxcr7 Activity In Human Glioblastoma Stem-likementioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that killer cell lectin-like receptor subfamily C, member 2 (KLRC2), a transmembrane activating receptor of natural killer cells, expressed higher in glioma-initiating cells compared with neural stem cell lines and normal adult brain tissue [36]. Emerging evidence suggests that the chemokine (C-X-C motif) ligand 12 (CXCL12), which is secreted from glioma stem cells (GSCs), plays a vital role in tumorigenesis and proliferation [37]. Additionally, many of the selected 26 functional pathways are related to the immune microenvironment, such as regulation of immune effector process, positive regulation of cytokine production, and cell chemotaxis.…”
Section: Discussionmentioning
confidence: 99%